2020
DOI: 10.1080/17549175.2020.1737181
|View full text |Cite
|
Sign up to set email alerts
|

Young people: being apart, together in an urban park

Abstract: Against the background of studies that report on urban park spaces as supporting inclusive city life and promoting tolerance and belonging, the present study investigated the spatial dimensions of gathering and othering in Wilhelminapark, Utrecht, the Netherlands. Using observational research and on-site group interviews, we found a diversity of users performing a diversity of activities. The presence of known or unknown visitors was given as an important reason to visit Wilhelminapark, although our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Previous qualitative research has found that while the presence of other people attracts adolescents to visit urban parks, minimal interaction between different user groups was often reported, and most adolescents kept to their social groups [ 69 ]. This suggests that co-presence with other user groups may not translate into meaningful contact, which may have been the case in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative research has found that while the presence of other people attracts adolescents to visit urban parks, minimal interaction between different user groups was often reported, and most adolescents kept to their social groups [ 69 ]. This suggests that co-presence with other user groups may not translate into meaningful contact, which may have been the case in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative research has found that while the presence of other people attracts adolescents to visit urban parks, minimal interaction between different user groups was often reported (51). This suggests that co-presence with other user groups may not translate into meaningful contact, which may have been the case in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…Finally, our research underscores that the health benefits of urban green spaces in low-income neighborhoods can only be realized when struggles over the social meanings of green spaces are taken seriously. Building on literature on the role of parks in stimulating contact between different (ethnic) groups, we found that although multilayered park narratives can be competitive, they are neither immutable nor mutually exclusive [ 31 , 32 , 44 ]. By fostering palpable experiences of being away, and by enabling interactions between strangers, citizen park interventions such as those described in our research can contribute to the transformation of low-income neighborhoods from places of decay to spaces of hope.…”
Section: Discussionmentioning
confidence: 99%
“…Like squares and streets, parks form an important part of the city’s public realm, which offers a setting for genuine and profound interaction [ 29 ]. In line with the urbanist idea of “the city as a stage” or “theater of social action,” recent studies have revealed parks to be popular sites for public realm interactions like play, public sociability, and people watching [ 30 – 32 ]. To public realm theorists, parks can provide a salutary and open environment for interactions between strangers and thereby foster experiences of equality and tolerance [ 33 ].…”
Section: Introductionmentioning
confidence: 99%